Planning for Post Disaster Recovery: Lesson Learnt from Flood Events in Kelantan Malaysia - Wan Mohd Rani, Wan Nurul Mardiah; Abdul Nifa, Faizatul Akmar; Ismail, Mohd Noorizhar; Khalid, Khairin Norhashidah (2017)
As the frequency of disaster occurrence increases, the world cities today are getting more difficult in terms of the management of the event. One of the most discussed issues today is the management of the post-disaster recovery that involves several stages such as the planning, management of multiple stakeholders, restoration, reconstruction and delivery. It is important to note that input from related stakeholders is necessary to make the right decision during this most critical period. In the process of building back after a disaster, it is important to ensure the newly constructed infrastructures are built to be more resilient and able to withstand a certain level of disaster recurrence. Elements of disaster risk reduction should be incorporated in the planning, redesign, construction and the operation of the built environment. In Malaysia, the disaster management has been the responsibility of the Disaster Management and Relief Committee that consists of agencies at the central, state and local levels. This is to ensure that all aspects are being considered and to be more effective in managing the situation